Habitat selection, population dynamics and breeding biology of the Rock Pipit Anthus spinoletta littoralis in southeastern Sweden - Larsson, Tommy (Ornis Svecica, 1994)
A population of breeding Rock Pipit Anthus spinoletta littoralis was studied in 1979—1990 in the archipelago off Oskarshamn in southeastern Sweden. Between 9 and 31 pairs were found breeding in the study area, at densities of 0.04–0.13 pairs/hectare in the different years. Population density declined abruptly between 1984 and 1985, probably due to harsh winter conditions. Territory size was usually 1–3 hectares. Average clutch size was 5.29 eggs/ clutch and 4.53 chicks/clutch. For their breeding Rock Pipits preferred habitats with stones, seaweed on the shoreline and a rich cover of low vegetation, to more barren habitats. Breeding success was higher in the preferred habitat.